Telomere A Complex End of a Chromosome - Larramendy, Marcelo L. (IntechOpen, 2016)
This book, Telomere - A Complex End of a Chromosome, is organized into nine chapters containing the latest aspects of the current knowledge about the structure of telomeres and the crucial role that telomerase plays not only in maintaining chromosomal stability but also in relation to cell immortality, cell instability, and cancer biology. We now appreciate that these unusual complexes of DNA and proteins we all know as "telomeres" are dynamic and key structures that depend on telomerase and other cellular factors for continuance. Regulation of telomere activity is a dynamic area of current research, and new insights into telomeres and their role in aging and cancer, among other biological functions and pathologies, appear regularly in the scientific world. However, one fact is more than understandable in this difficult biological conundrum: the end of the telomere story is far from being totally unraveled.